Corporate Governance Moderates Tax Avoidance Determinants in Transportation Firms: Tata Kelola Perusahaan Memoderasi Faktor Penentu Penghindaran Pajak di Perusahaan Transportasi - Mei Dwi Wulandari; Herman Ernandi (Academia Open, 2025)
General Background: Tax avoidance remains a contentious issue in corporate financial management, drawing extensive academic and regulatory attention. Specific Background: While prior studies have examined the role of firm characteristics on tax behavior, limited attention has been given to the moderating effect of corporate governance.Knowledge Gap: Few empirical studies integrate internal company factors with governance mechanisms to explain variability in tax avoidance, especially in Indonesia’s transportation manufacturing sector. Aims: This study investigates the effects of leverage, firm size, thin capitalization, corporate social responsibility (CSR), and capital intensity on tax avoidance, and evaluates whether corporate governance—proxied by independent commissioners—modulates these relationships. Results: Using Smart-PLS analysis on data from 2019–2023, we find that firm size, thin capitalization, and capital intensity significantly influence tax avoidance, whereas leverage and CSR do not. Novelty: The study introduces a moderating analysis revealing that corporate governance can either amplify or dampen the influence of firm size, CSR, and capital intensity on tax avoidance—highlighting a nuanced role for governance mechanisms.Implications: These findings underscore the strategic role of independent commissioners in mitigating aggressive tax practices and offer insights for regulators aiming to improve corporate tax compliance through governance reforms. Highlights: Highlights the moderating role of independent commissioners in tax strategies. Reveals that firm size, thin capitalization, and capital intensity significantly impact tax avoidance. Offers evidence-based insights from Indonesia’s transportation manufacturing sector (2019–2023). Keywords: Tax Avoidance, Corporate Governance, Firm Characteristics, Capital Intensity, Independent Commissioners